School staff perpetration of physical violence against students in Uganda: a multilevel analysis of risk factors. Issue 8 (18th August 2017) - Merrill, Katherine G; Knight, Louise; Glynn, Judith R; Allen, Elizabeth; Naker, Dipak; Devries, Karen M
Abstract : Objective: To conduct a multilevel analysis of risk factors for physical violence perpetration by school staff against Ugandan students. Design: Multilevel logistic regression analysis of cross-sectional survey data from 499 staff and 828 caregivers of students at 38 primary schools, collected in 2012 and 2014 during the Good Schools Study. Setting: Luwero District, Uganda. Main outcome measure: Past-week use of physical violence by school staff against students was measured using the International Society for the Prevention of Child Abuse and Neglect 'Child Abuse Screening Tool- Child International' and the WHO Multi-Country Study on Women's Health and Domestic Violence against Women. Results: Of 499 staff, 215 (43%) reported perpetration of physical violence against students in the past week. Individual risk factors associated with physical violence perpetration included being a teacher versus another type of staff member (p<0.001), approving of physical discipline practices (p<0.001), having children (p<0.01), being age 30–39 years (p<0.05), using physical violence against non-students (p<0.05) and being a victim of intimate partner violence (IPV) (p<0.05). We observed weak evidence (p=0.06) that male staff members who had been a victim of IPV showed higher odds of violence perpetration compared with male staff who had not been a victim of IPV. No evidence was observed for school- or community-level risk factors. Conclusions: Physical violence perpetration from school staff is widespread, and interventions are needed to address this issue. Staff who have been victims of violence and who use violence against people other than students may benefit from additional interventions. Researchers should further investigate how school and community contexts influence staff's physical violence usage, given a lack of associations observed in this study.